Analisis dan Perancangan Aplikasi Kepuasan Klien Berdasarkan Model Servqual (Studi Kasus: PT. Longvin Indonesia) - Cecep Kurnia Sastradipraja; Aris Subagja; Dea Kris Sintiana Putri; Haerul Ramadan; Raziya Mutasim (Justek : Jurnal Sains dan Teknologi, 2019)
This research aims to analyze and develop service quality information systems on client satisfaction at PT. Longvin. This is because of PT. Longvin in processing service evaluations, assessing and distributing questionnaires which were still carried out manually so that in general it allowed for limitations and shortcomings such as piling up of files, incomplete questionnaire data filling, slow data processing, and could result in inaccurate decisions.The process of developing information systems using the waterfall model includes requirements analysis, system analysis, system modeling through defining context diagrams, data flow diagrams and entity relationship diagram. At the implementation stage, the system is oriented to the web environment using the programming languages PHP and MySQL as database management. For the analysis of service quality measurement using the servqual model. In the system, testing is carried out using BlackBox testing, while end-user testing is based on the results of questionnaire data processing using the Likert scale model.Based on the observation that the system can display the results of service quality calculations quickly and depicted through detailed graphs, total tables, average tables, and automatic suggestions. The results of system testing on end users show that the application built is very good with a percentage of 82% giving an agreed assessment.